Telaah Problematika Perceraian (Thalaq) Perspektif Asghar Ali Engineer - Ahmad Nailul Fauzi (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2019)
This article explains the thoughts built by Asghar Ali Engineer. The author focuses on one of the major sub-themes in the book The Qur’an Women and Modern Society, namely divorce in the Qur’an and Shari’ah. According to Asghar Ali Engineer, legal experts have agreed to a divorce that is still exclusive in the area of men. Basically, in the Qur’an there is no such explicit statement. Thus only conclusions, not holy rules, are interpreted by medieval scholars of QS. Al-Qur’an al-Baqarah 2: 237. According to him, there are several verses of the Qur’an about divorce which according to Asghar are not relevant to the current context, only at the time of the Prophet. The object of the study in this study is to describe the methodology of Asghar in interpreting verses about divorce. Furthermore, from the explanation of Asghar Ali Engineer who has been detailed, indeed he has used the method he built, namely liberation theology, which this time focused on the theme of gender equality. The concept that he built can be broken down by the model of liberative-sociological normative interpretation.